Pengaruh Store Atmosphere Terhadap Impulse Buying Yang Dimoderasi Oleh Faktor Mashlahah - Fitria Astari; Ismail Ismail; Anne Putri (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2019)
The aim of this research is to analyze the influence of store atmosphere on impulse buying which is moderated by mashlahah factor. This research tries to investigate the role of mashlahah factor in affecting relationship between store atmosphere and impulse buying. The study population is all visitors of fashion retail stores in Bukittinggi. Sampling method used in this research is purposive sampling method, final sample counted 152 respondents. The study used a moderated regression analysis (MRA) tool with the SPSS program to test the hypothesis.The findings showed that store atmosphere variable positively affect the impulse buying. The results also prove the mashlahah factor negatively moderating the relationship between store atmosphere and impulse buying.